Green Financing and Development Opportunities - Abdikarimova Aynura Abay qizi (Genius Journals, 2024)
This article describes green financing and its development opportunities. That is, green bonds, as a new financial instrument in the stock market, differ from other instruments in that they are aimed at financing environmentally beneficial projects, renewable energy projects, energy efficiency improvement, and the use of environmentally friendly transport
Keywords: Green economy; green financing; green bond